2010
DOI: 10.5897/jmpr10.407
|View full text |Cite
|
Sign up to set email alerts
|

Antispermatogenic effects of aqueous ethanolic extract of Hymenocardia acida stem bark in Wistar rats

Abstract: Oral administration of aqueous ethanolic extract of Hymenocardia acida stem bark for eight weeks caused a significant reduction (P < 0.05) in the weights of testes, epididymides, ventral prostrate, seminal vesicles and vasa differentia compared to the control. The treatment related decreases in sperm motility, count, viability and serum testosterone returned to near normal levels on withdrawal of the extract. The groups that received doses of 100, 200 and 400 mg/kg body weight of the extract showed 40, 0 and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
4
12
1
Order By: Relevance
“…This lowered fertility index could be attributed to the summation of the effects of the extract on the parameters analyzed, the contractile effect of the extract and the possible toxicity associated with the extract. Similar observations on reduced fertility indices were made when pregnant rats were treated with Dalbergia axatilis (Uchendu et al, 2000) and Hymenocardia acida (Abu and Uchendu, 2011).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This lowered fertility index could be attributed to the summation of the effects of the extract on the parameters analyzed, the contractile effect of the extract and the possible toxicity associated with the extract. Similar observations on reduced fertility indices were made when pregnant rats were treated with Dalbergia axatilis (Uchendu et al, 2000) and Hymenocardia acida (Abu and Uchendu, 2011).…”
Section: Discussionsupporting
confidence: 65%
“…Toxicity of the kidney cells has also been recorded in an attempt to induce abortion on days 15 and 16 using 500 mg/kg body weight of ethanolic fruit extract of Picralima nitida (Mbegbu et al, 2014b). A reduction in FCRL in the treated pregnant rats as observed in the present study had also been reported when Acanthus montanus leaves extract (Nana et al, 2008) and Hymenocardia acida stem bark extract (Abu and Uchendu, 2011) were administered to pregnant rats. The significant difference in the body weights of the rats treated with 500 mg/kg body weight is simply a reflection of the significant reduction in the mean live foetal number (LFN) and foetal crown rump length (FCRL).…”
Section: Discussionsupporting
confidence: 63%
“…Also, Yamauchi et al (1992); showed almost equal inhibitory effects of grapes from different places of Japan, China, Brazil and USA. Banskota et al (2000) obtained same results for nine different grape samples from Brazil, Peru, the Netherlands and China.…”
Section: Discussionsupporting
confidence: 55%
“…Flavanones (e.g., myricetin, hesperidin, naringin and naringenin) (Peterson and Dwyer, 1998). Flavonoids have been reported to have in vivo and in vitro antioxidant activities through their ability to scavenge the radicals of hydroxyl, peroxyl, superoxide, nitric2 oxide and DPPH (2,2-diphenyl-1-picrylhydrazyl) (Awah and Verla, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hymenocardia acida on the other hand has an antioxidant activity [12] and pro-oxidant activity [15]. The result of this study show that aluminum chloride did not cause significant (p<0.05) difference in testosterone levels of the rats.…”
Section: Discussionsupporting
confidence: 54%